Biomechanical Device for Strength Control in Dental Restorations. (24th June 2020) - Esteves, M; Falacho, R; Silva, M; Roseiro, L
Abstract: Introduction In the dentistry field, restoration of a damaged tooth using indirect restorations is a common activity. In the restoration process with cementing agents, there is a need to apply force to the insertion of the part that will rehabilitate the tooth. This force becomes essential to cause the flow of the cementitious material, thus improving the prognosis and longevity of the restoration-tooth assembly. Excessive force can cause damage and a little intensity force will not be enough for the correct seating of the piece. However, the applied force is dependent on the sensitivity of the dentist, and there are no tools that guarantee the aid in its monitoring. Objectives The biomechanical device must be able to monitor the forces applied on teeth restoration and has its importance based in clinical environment use, but above all will be a relevant tool in the learning process for dental medicine students. Methodology The developed device is based on some commonly used dental systems for dental restorations. A geometry was created using a computer aided design software and calculated by the finite element method. The developed solution uses the structural information for force control with strain gauges. The equipment interacts with the user using incorporated sound and light signals powered by a battery, but also can be wired to a computer. Results The medical team performed some tests in ceramic teeth samples, in order to ensure the reality of the tests. The device operation reveals an easy and stable force application as well as a correct sound and light feedback. After the sample's analysis, the cement thickness and strength are within ideal parameters. Conclusion From this work resulted the invention of a functional biomechanical equipment that will be used in student learning process and in clinical context. The device had a good acceptance and feedback by the medical team, promising to revolutionize the way dental restorations are performed.